The Initial Screening of Heavy Metal Adsorption on Highly Porous Metal-Organic Frameworks based on MIL-101(Cr), Ethylenediamine-modified MIL-101(Cr), and MIL-101(Cr)-NH2 - Dendy, Dendy; Lestari, Witri Wahyu; Anshori, Isa; Rahardjo, Sentot Budi; Pramono, Edi; Saraswati, Teguh Endah; Wibowo, Fajar Rakhman (Molekul, 2026)
ABSTRACT. Heavy metal pollution is a significant environmental issue with detrimental effects on ecosystem and human health. Therefore, comprehensive handling need to be carried out. Herein we studied initial screening adsorption of heavy metals including Ni, Cu, Zn, Cd, and Pb using Metal-Organic Frameworks class of Materials Institute Lavoisier (MIL) based on Cr(III). MIL-101(Cr), and its modification with ethylenediamine (EA), and MIL-101(Cr)-NH2 were prepared under hydrothermal condition. X-ray diffraction and FT-IR analysis confirmed the formation of the targeted materials. A new absorption band at 1050 cm-1 corresponds to vibration of C-N which indicates the successful EA modification into MIL-101(Cr). Nitrogen sorption isotherm measurement revealed MIL-101(Cr) and EA@MIL-101(Cr) have a specific surface area of 2548.6 and 2079 m²/g with micropore-sized, while MIL-101(Cr)-NH2 has a specific surface area of 1583.4 m²/g with micro and mesopore-sized. Adsorption performance was assessed through batch experiments monitored by atomic absorption spectroscopy. The results show that MIL-101(Cr) and its modification with EA exhibit higher adsorption capacities on cadmium and nickel metal ions, compared to MIL-101(Cr)-NH2. Meanwhile, MIL-101(Cr)-NH2 and MIL-101(Cr) show more dominant adsorption capabilities on zinc and copper ions compared to the EA-modified MIL-101(Cr). This result suggests that the material's porosity still plays a dominant role in the adsorption processes compared to amine functionalize group on MIL itself. Keywords: adsorption, chromium(III), heavy metals, MOF, MIL